A study of factors affecting the success rate of type-1 tympanoplasty - Bhadesia, Bhoomi; Joshi, Hetal; Desai, Nisarg; Hirani, Narendra; Khilnani, Ajeet Kumar; Sorathiya, Rashmi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic otitis media (COM) (tubo-tympanic) is a common ear pathology for which tympanoplasty is done. Factors that affect the success rate of tympanoplasty can be patient related (age, gender, socio-economic status), disease related (duration and severity of symptoms) or technique related (equipment and surgical approaches). This study was undertaken to know the factors affecting success rate of type-1 tympanoplasty at our institute. Methods: This was a prospective observational study conducted at ENT Department of Gujarat Adani Institute of Medical Sciences, Bhuj, from October 2017 to July 2019. All patients between 20 and 60 years of age with inactive mucosal COM operated for type-1 tympanoplasty were included in the study. Pre-operative, intra-operative and post-operative details were recorded as per the pre validated proforma and evaluated using Chi-square and paired t-test. Results: 100 patients were included in our study. Females were more commonly affected (61%) than males (39%). In 78% of patients one ear was affected (left 40%, right 38%). Ear discharge was the most common symptom (99%). Maximum patients (55%) had a moderate perforation. The perforation was central in all cases. Microscopic surgery was done in 79% of patients. Post aural approach (Wilde’s incision) was the most common approach used (70%). The most common graft material used was temporalis fascia (96%). In 61% of patients graft was kept by underlay technique. Conclusions: In our study, the success rate of tympanoplasty was significantly more when duration of discharge was less, microscope was used for surgery and post aural approach was used. Success rate was less when there was history of any previous nasal pathology. Other factors, like age, gender, socio-economic class, occupation, side of involvement of ear, size and site of perforation and grafting techniques, did not affect the success rate of tympanoplasty.